Study of the Statistical Characteristics of Artificial Source Signals Based on the CSES - Huang, Jianping; Jia, Juan; Yin, Huichao; Li, Zhong; Li, Jinwen; Shen, Xuhui; Zhima, Zeren (Frontiers in Earth Science, 2022)
The ground-based artificial source electromagnetic signal transmitted to space will form a pair of intensity regions over the station and its conjugate point. In order to study the position and intensity of the strongest points in the two regions, the power-spectrum density (PSD) of the electric field on board the Zhangheng-1 satellite (CSES) was selected when it passed over the NWC artificial source transmitting station. The selected frequency is centered at 19.8 kHz with a bandwidth of 200 Hz. The strongest point is defined as the location with the maximum power spectral density of ±10° around the NWC station within 5 days, which is the revisiting period of the CSES. The results show that statistical characteristics of strongest points vary as day/night, local/conjugate point, longitude/latitude, and different components of electric field vectors. In terms of longitude deviation, it is mostly westward offset at night and on both sides in the day over the NWC but opposite at the conjugate point. In terms of latitude deviations, it is equator-ward at night and the same during the day with a smaller deviation. While over the conjugate point, it is northward offset in the day and both at night with a bigger offset. In terms of intensity, it is stable without obvious seasonal changes over the NWC and its conjugate point. The intensity of PSD is higher at night than during the day. For the PSD intensity of the three components, the descending order over the NWC is Ead, Eab, and Ecd at night and Ecd, Ead, and Eab in the day, and the opposite is true for over the conjugate point.